The Application of The Principles of Legal Assurance, Justice, And Expediency in State Civil Apparatus Dishonorable Discharge a Study of Civil Court Judgment Number 164/G/2019/Ptun-Jkt - Khozin Alfani (Faculty of Law, Musamus University, 2022)
Justice is the essence of law. Its existence must be in line with legal assurance and legal expediency. The slow execution of the government in carrying out the order of the State Civil Apparatus Law for the dishonorable discharge of state civil apparatus employee because of the malfeasance they committed raises the problem of substantive justice. The judges’ verdict of the Jakarta Civil Court that adjudicated the dispute regarding the dishonorable discharge, granted the request of the concerned civil servant. This study aims to analyze the application of the principles of legal certainty, justice, and expediency in the judge verdict of the Civil Court no. 164/G/2019/PTUN-JKT. The research method is in the form of juridical, mainly from secondary data, exploratory analytical typology with a qualitative approach. The results of the study show that judges apply the principles of legal assurance, justice, and expediency in a balanced manner by considering the chronology and legal facts in the process of civil servant dishonorable discharge. At the same time correcting the government's legal actions by elaborating the principles contained in positive law.